2014
DOI: 10.1089/thy.2013.0287
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Changes and Increased Expression of Myxovirus Resistance Protein A in Thyroid Tissue of Patients with Recent Onset and Untreated Graves' Disease

Abstract: The increase in CD8+ T cells during the chronic stage of GD suggests that they may play a role in progression of the autoimmune process from early to chronic thyroiditis. Upregulation of MxA expression during the early stages of the disease, and the positive correlation between the number of PDCs and the number of MxA+ leucocytes, suggests that activated PDCs secrete type I IFNs at the lesion site, possibly in response to viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The development of GD is influenced by various genetic and environmental factors and the interactions between them (1). GD pathogenesis is generally characterized by abnormalities in T-cell subsets (2,3), innate immune cells (4), and various cytokines, which ultimately decreases immune tolerance and excessively activates B cells, promoting the production of thyroid stimulating hormone (TSH) receptor antibody (TRAb). The biased activation of helper T (Th) cells has an important role in GD development (5,6) and the imbalance of Th1/Th2 cell immunity may result in a shift toward the Th2-type immune response (7).…”
Section: Introductionmentioning
confidence: 99%
“…The development of GD is influenced by various genetic and environmental factors and the interactions between them (1). GD pathogenesis is generally characterized by abnormalities in T-cell subsets (2,3), innate immune cells (4), and various cytokines, which ultimately decreases immune tolerance and excessively activates B cells, promoting the production of thyroid stimulating hormone (TSH) receptor antibody (TRAb). The biased activation of helper T (Th) cells has an important role in GD development (5,6) and the imbalance of Th1/Th2 cell immunity may result in a shift toward the Th2-type immune response (7).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of GD is mainly attributed to genetic factors; however, GD can be triggered by environmental factors, such as infection (Hammerstad et al, 2013(Hammerstad et al, , 2014 and psychological trauma (Vita et al, 2014). The exact cause of GD however remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence analysis of thyroid specimens confirmed the presence of CD303 + CD123 + CD83 -immature pDCs typically in close contact with lymphocytes, as well as CD11c + cDCs, which were also identified as a potential local source of IFNa [43]. Disease stage dependent changes in the structure of thyroid immune infiltrates was also shown by Hammerstad and colleagues in immunostaining assays of thyroid tissue obtained both from HT [44] and GD patients [45]. In the newly diagnosed untreated GD patients, the authors observed a significant increase of thyroid pDC population, as compared with chronic GD and healthy subjects.…”
Section: Cd8amentioning
confidence: 55%
“…In the newly diagnosed untreated GD patients, the authors observed a significant increase of thyroid pDC population, as compared with chronic GD and healthy subjects. Importantly, the number of pDCs correlated with the expression of interferon-inducible Myxovirus Resistance Protein A (MxA) regarded as a marker of IFN I production [45]. Similar increase in thyroid pDCs population and MxA expression was observed in HT patients.…”
Section: Cd8amentioning
confidence: 64%
See 1 more Smart Citation